Exploring A Pocket Guide to Writing through Cultural-Historical Activity Theory: Implications for Multicultural Education - Rouabhia, Ridha (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Mainstream writing instruction risks marginalising non-dominant voices if not consciously adapted using critical multicultural frameworks. This study analyses Mary Lynn Rampolla's widely used A Pocket Guide to Writing in History through a Cultural-Historical Activity Theory (CHAT) lens, taking notes on voice, power dynamics, and participation elements. The analysis uncovered alignments like the focus on active reading and argumentation. However, tensions emerged regarding the lack of collaborative learning and critical framing of academic conventions. Findings suggest that relying solely on mainstream writing advice risks student empowerment and critical consciousness deficiencies. Writing instructors should supplement individual skill-building with critical perspectives and participatory activities. While conventional guides provide useful starting points, realising the transformative goals of critical multicultural education requires balancing mainstream approaches with conscious efforts to incorporate collaboration, student voice, and critical framing. Further research should build on this study to strengthen writing pedagogy for diversity and equity. It could involve collaborative ethnographic studies in diverse classrooms to examine real-world applications, affordances and limitations. Additionally, studies comparing findings across guides using critical frameworks like CHAT, Critical Race Theory and Critical Discourse Analysis could offer a deeper analysis of patterns and equity implications.